Therapeutic Efficacy of Excretory-Secretory Products of Trichinella spiralis Adult Worms on Sepsis-Induced Acute Lung Injury in a Mouse Model - Li, Huihui; Qiu, Dapeng; Yang, Huijuan; Yuan, Yuan; Wu, Lingqin; Chu, Liang; Zhan, Bin; Wang, Xiaoli; Sun, Yan; Xu, Wei; Yang, Xiaodi (Frontiers in Cellular and Infection Microbiology, 2021)
Acute lung injury (ALI) is a common complication of systemic inflammation or sepsis with high morbidity and mortality. Although many studies have confirmed that helminth-derived proteins had strong immunomodulatory functions and could be used to treat inflammatory diseases, there is no report on the therapeutic effect of excretory-secretory products of Trichinella spiralis adult worms (Ts-AES) on sepsis-induced ALI. In this study, the therapeutic efficacy of Ts-AES on sepsis-induced ALI and the underlying immunological mechanism and the signaling pathway were investigated. The results indicated that after being treated with Ts-AES, the survival rate of mice with CLP-induced sepsis was significantly increased to 50% for 72 hours after CLP surgery compared to PBS control group with all mice died. The sepsis-induced ALI was largely mitigated characterized by reduced inflammation cell infiltration and pathological changes in lung tissue, with decreased lung injury scores and lung wet/dry weight ratio. The therapeutic efficacy of Ts-AES is associated with stimulated Tregs response with increased regulatory cytokines IL-10 and TGF-β and downregulated pro-inflammatory cytokines (TNF-α, IL-6, IL-1β). The expression of HMGB1, TLR2 and MyD88 in lung tissue was inhibited after treatment of Ts-AES. Our results demonstrated that Ts-AES play an important role in immunomodulation and confer a therapeutic effect on sepsis-induced ALI through inhibiting pro-inflammatory cytokines. The activation of Tregs and increased level of regulatory cytokines IL-10 and TGF-β are possibly involved in the immunomodulatory functions of Ts-AES through HMGB1/TLR2/MyD88 signal pathway. The findings suggest Ts-AES is a potential therapeutic agent for prevention and treatment of sepsis-induced ALI and other inflammatory diseases.